Effect of boron on microstructure, thermal, and mechanical properties of Ni B matrix diamond cutting tools - Islak, Serkan; Celik, Ertugrul; Houssain, Hasaneen; Danaci, Hacer Cemre (Elsevier BV, 2024)
This study examines the impact of adding boron on the microstructural, thermal, and mechanical properties of Ni-B alloy matrix diamond cutting segments, which are created using the hot pressing process. Microstructure was investigated using SEM-EDS and XRD analysis. The high-temperature oxidation behavior of the samples was determined by thermogravimetric analysis. The hardness was quantified employing Vickers hardness testing, as well as, sample densities were derived based on Archimedes' principle. The wear resistance was evaluated using the reciprocating wear test method. A three-point bending test was used to examine how the diamond grains were retained inside the Ni-B matrix. The XRD investigations identified the formation of Ni, Ni3B, and Ni2B phases. The thermogravimetric analysis results showed that Ni-B alloys were exposed to oxidation at elevated temperatures as the B content increased, However, a hardness improvement was observed as the B content increased due to the formation of borides. Furthermore, the tribological investigation reveals that adding the B as reinforcement has a positive effect at a specific amount, where the optimal wear resistance and minimal friction coefficient were evident at 6% B contained sample.